A Concussion Education Programme for Motorsport Drivers: A Field-Based Exploratory Pilot Study. (29th July 2021) - Adams, Stephanie A.; Richards, Hugh; Sproule, John; Hutchinson, Peter J.; Turner, Anthony P.
ABSTRACT: Objective: Concussion education strategies that improve knowledge and attitudes long term are needed. This exploratory study piloted an interactive concussion education program, adopting concepts from the learning sciences and attitude change literature, for the underserved and high-risk population of motorsports. Method: Forty UK motorsport drivers (ages 16–20 years) participated. The workshop group received a two-phased workshop-based program. The comparison group received a concussion leaflet. Participants completed an adapted version of the Rosenbaum Concussion Knowledge and Attitudes Survey (RoCKAS-ST) at pre-, post- and 2-month follow-up. Within-group analysis for the workshop group explored the differential effect of the individual difference variable, Need for Cognition (NfC), and effectiveness was explored through post-workshop questionnaires and interviews. Results: Unlike the comparison group, the workshop group showed a significant improvement in knowledge over time ( F (2, 58) = 45.49, p < .001, η2 p = .61). Qualitative data indicated workshop-program participants developed safer attitudes toward concussion following programming. Preliminary evidence suggested individuals' responses to concussion education aligned with differences in NfC. Conclusion: This study piloted the first concussion education program for motorsport drivers and explored whether aligning educational provision with the NfC construct may help to improve program effectiveness. Findings are relevant to addressing the public health issue of concussion through educational approaches.